Price Elasticity of the Residential Water Demand. Case-Study: Investment Project in Cluj County, Romania - Vasile Iuliu CIOMOŞ; Dorin Marcel CIATARÂŞ; Alina Oana CIOMOŞ (Transylvanian Review of Administrative Sciences, 2012)
In Romania, local authorities and the newly established Regional Operators one of them being S.C. Compania de Apă Someş S.A., are required to fully comply with EU regulations concerning water and wastewater quality. In order to meet these requirements in due time, a lot of investment projects have to be prepared and implemented. The financing of these investments requires a progressive increase of the tariffs. In the last ten years, in Romania, the tariffs for the water services have been significantly augmented, more than in any other East European country. In the same time, a substantial reduction of the residential water consumption, measured in liters per capita per day, has been observed. In this article, the price elasticity of residential water demand for water services was analyzed, given its importance in the framework of the feasibility studies for investments to be made in order to insure compliance with EU water and wastewater Directives. In the same time, considerations with regard to the evolution of the tariff for water services and of the residential water demand are provided, with the aim of better explaining the context in which these variables evolve.